1999
DOI: 10.1109/4.753687
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of master-slave latches and flip-flops for high-performance and low-power systems

Abstract: In this paper, we propose a set of rules for consistent estimation of the real performance and power features of the flip-flop and master-slave latch structures. A new simulation and optimization approach is presented, targeting both highperformance and power budget issues. The analysis approach reveals the sources of performance and power-consumption bottlenecks in different design styles. Certain misleading parameters have been properly modified and weighted to reflect the real properties of the compared str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
251
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 514 publications
(253 citation statements)
references
References 13 publications
1
251
1
Order By: Relevance
“…Post-layout simulations showed that the kit's estimates for small designs are often conservative and that compact circuits often perform slightly faster in post-layout simulations than in schematic simulations with the automatic parasitic network estimation turned on. The simulation test bench that is used in this comparison is very similar to the ones used in [5], [13], [14]. The Q output of a simulated flip-flop is connected to a load of four symmetric inverters with their n-type transistors sized at minimum recommended width.…”
Section: Previous Work Existing Methodsmentioning
confidence: 99%
“…Post-layout simulations showed that the kit's estimates for small designs are often conservative and that compact circuits often perform slightly faster in post-layout simulations than in schematic simulations with the automatic parasitic network estimation turned on. The simulation test bench that is used in this comparison is very similar to the ones used in [5], [13], [14]. The Q output of a simulated flip-flop is connected to a load of four symmetric inverters with their n-type transistors sized at minimum recommended width.…”
Section: Previous Work Existing Methodsmentioning
confidence: 99%
“…To implement it, a modular design has been developed based on the cell in Fig 1b. The circuit has been designed using the AMS standard 0.35 µm CMOS library. Although power consumption and noise generation strongly depends on the kind of flip-flops used [6,7] our goal is to explore what improvements can be done in a counter with a given flip-flop.…”
Section: The Counter and The Measurement Methodologymentioning
confidence: 99%
“…At present, we have layout/circuit models for a simple dual bitline SRAM cell, a multi-ported (4r,2w) SRAM cell, a simple CAM cell, an ALU bit slice, and a pipeline latch comparable to one used in the PowerPC 603 [32]. As we continue the development of VariPower, we hope to extend this list to cover more circuits.…”
Section: Low Level Circuit Blocksmentioning
confidence: 99%